Recent Advances in Glioma Therapy: Combining Vascular Normalization and Immune Checkpoint Blockade - Ho, Rachel L. Y.; Ho, Ivy A. W. (Cancers, 2021)
Glioblastoma (GBM) accounts for more than 50% of all primary malignancies of the brain. Current standard treatment regimen for GBM includes maximal surgical resection followed by radiation and adjuvant chemotherapy. However, due to the heterogeneity of the tumor cells, tumor recurrence is often inevitable. The prognosis of patients with glioma is, thus, dismal. Glioma is a highly angiogenic tumor yet immunologically cold. As such, evolving studies have focused on designing strategies that specifically target the tyrosine kinase receptors of angiokines and encourage immune infiltration. Recent promising results from immunotherapies on other cancer types have prompted further investigations of this therapy in GBM. In this article, we reviewed the pathological angiogenesis and immune reactivity in glioma, as well as its target for drug development, and we discussed future directions in glioma therapy.